2012
DOI: 10.1111/j.1365-246x.2012.05627.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there a normal magnetic-polarity event during the Palaeocene-Eocene thermal maximum (∼55 Ma)? Insights from the palaeomagnetic record of the Belluno Basin (Italy)

Abstract: SUMMARY In the lowermost Eocene sedimentary record of Ocean Drilling Program Site 1262 (Leg 208, Walvis Ridge, South Atlantic Ocean), the presence of a ∼53‐kyr‐long normal polarity event has been recorded within the ∼2.55‐Myr‐long reverse polarity Chron C24r (∼53.3–55.9 Ma) and termed Palaeocene–Eocene magnetic reversal (PEMR). The origin of the PEMR has been speculatively related to a change in the Earth's rotation rate that was in turn influenced by an abrupt overturning of the ocean‐atmosphere circulation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
3
7
0
Order By: Relevance
“…At Terche, the intensity of the NRM ranges from 1.08 × 10 −4 to 1.14 × 10 −3 Am −1 , with an average value of 3.03 × 10 −4 Am −1 (Figure ), in agreement with the data from the coeval part of the Cicogna section [ Dallanave et al , , , ]. The unblocking temperature indicates a magnetization carried by hematite, in agreement with the results obtained from the Cicogna section sediments.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…At Terche, the intensity of the NRM ranges from 1.08 × 10 −4 to 1.14 × 10 −3 Am −1 , with an average value of 3.03 × 10 −4 Am −1 (Figure ), in agreement with the data from the coeval part of the Cicogna section [ Dallanave et al , , , ]. The unblocking temperature indicates a magnetization carried by hematite, in agreement with the results obtained from the Cicogna section sediments.…”
Section: Resultssupporting
confidence: 87%
“…The magnetic mineralogy and rock‐magnetic properties of the Paleogene sediments of the Belluno Basin have been extensively investigated by Dallanave et al . [, , , ]. In particular, detailed paleomagnetic and rock‐magnetic study of the lower Eocene sediments of the Cicogna section [ Dallanave et al , , ] revealed that the dominant magnetic mineral is detrital hematite, which coexist with minor maghemite.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the IRM drop is interpreted as reflecting inversion of γ‐Fe 2 O 3 to α‐Fe 2 O 3 during heating in the magnetic field‐free furnace. Similar curves have been obtained from correlative sediments from southern New Caledonia (Dallanave et al, 2018) and coeval hemipelagic red beds from the Italian Alps (Dallanave et al, 2009, 2010, Dallanave, Agnini, et al, 2012, Dallanave, Muttoni, et al, 2012). In the latter cases, the maghemite‐hematite transition is observed at lower temperatures, approximately between 300°C and 400°C.…”
Section: Resultssupporting
confidence: 73%
“…Detrital hematite sharply increased in concentration at the onset of Assemblage E Dallanave et al, 2010Dallanave et al, , 2012Fig. 4).…”
Section: Climate and Deep Sea Life During The Core Of The Cie And Recmentioning
confidence: 97%
“…A common obstacle to performing detailed high-resolution studies of the PETM in deep-sea sediments is the fact that many records are condensed or discontinuous, especially across the few thousand years (Zeebe et al, 2014) of the onset of the carbon isotope excursion. The Forada section (northeastern Italy) represents an outstanding exception in that it contains an expanded deep-sea record of the PETM, which has been extensively studied because of its continuity and cyclostratigraphy (Agnini et al, 2007;Luciani et al, 2007;Tipple et al, 2011;Dallanave et al, 2012). Carbonate dissolution is less severe at Forada than in many other sections, with calcareous benthic foraminifera present for most of the interval characterized by the CIE (> 4 m; .…”
mentioning
confidence: 99%